The Effect of Unsatisfied Experience, Culture Value, and Value Loss on Complaint Intention of Electronic Devices in Bogor, West Java, Indonesia - Rizky Perdana Putra; Lilik Noor Yuliati (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2016)
Purchase dissatisfaction on electronic devicescould cause complaint intention.Besides purchase dissatisfaction, culture values included individualism and collectivsm also influenced complaint intention. The aim of this study was to analyze the effect of unsatisfied experience, culture value, and the value loss on complaint intention of electronic devices. The location of this study was selected purposivelywhich was Paledang District, Central Bogor Regency, Bogor City. The study involved 100 respondents which were selected purposively. The respondents were a husband or a wife who made a decision on buying and using electronic devices. The data werecollectedwith an interview using questionnaire. The result showed that unsatisfied experience, individualism, and age influenced complaint intention while collectivism, value loss, and family income were the factors which did notinfluence complaint intention. Keywords: culture values, collectivism, individualism, complaint intention, value loss,unsatisfied experienceKetidakpuasan pembelian barang elektronik dapat menimbulkan adanya niat komplain.Selain ketidakpuasan, culture value juga memengaruhi seseorang berniat untuk melakukan komplain. Culture value dalam penelitian ini meliputi individualisme dan kolektivisme. Penelitian ini bertujuan untuk menganalisis pengaruh pengalaman ketidakpuasan, culture value, serta nilai kerugian terhadap niat komplain pada barang elektronik. Pemilihan lokasi penelitian dilakukan secara purposif yaitu di Kelurahan Paledang RW 04, Kecamatan Bogor Tengah, Kota Bogor. Penelitian melibatkan 100 orang sebagai sampel yang dipilih secara purposif, yaitu suami atau istri yang mengambil keputusan dalam membeli barang elektronik. Data diperoleh melalui wawancara dengan menggunakan kuesioner. Hasil penelitian menunjukkan bahwa pengalaman ketidakpuasan, individualisme, dan usia memiliki pengaruh terhadap niat komplain sedangkan kolektivisme, nilai kerugian, dan pendapatan keluarga merupakan faktor-faktor yang tidak berpengaruh terhadap niat komplain. Kata kunci: culture values, individualisme, kolektivisme, niat komplain, nilai kerugian, pengalaman ketidakpuasan